2000
DOI: 10.1126/science.287.5450.125
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Brain Reward Circuitry by Leptin

Abstract: Leptin, a hormone secreted by fat cells, suppresses food intake and promotes weight loss. To assess the action of this hormone on brain reward circuitry, changes in the rewarding effect of lateral hypothalamic stimulation were measured after leptin administration. At five stimulation sites near the fornix, the effectiveness of the rewarding electrical stimulation was enhanced by chronic food restriction and attenuated by intracerebroventricular infusion of leptin. In contrast, the rewarding effect of stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
235
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(261 citation statements)
references
References 31 publications
20
235
0
6
Order By: Relevance
“…17 It is interesting that obese rats showed increased motivation for sucrose while having increased leptin concentrations. Leptin has been shown to reduce the rewarding effect of lateral hypothalamic self stimulation at food sensitive sites, 31,32 and recently it has been shown that leptin affects mesoaccumbens dopamine signaling. 33,34 This suggests a role for leptin in the modulation of brain reward mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 It is interesting that obese rats showed increased motivation for sucrose while having increased leptin concentrations. Leptin has been shown to reduce the rewarding effect of lateral hypothalamic self stimulation at food sensitive sites, 31,32 and recently it has been shown that leptin affects mesoaccumbens dopamine signaling. 33,34 This suggests a role for leptin in the modulation of brain reward mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…35 Rats that were relatively insensitive to leptin's anorexigenic effect were more prone to obesity when fed a high-fat diet. 36 Because leptin-sensitive neurons are also present in areas important for reward mechanisms, 31,32,37 it would be interesting to study whether the leptin sensitivity and the motivation to press for sucrose that both predict future obesity are related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the lateral hypothalamic area (LHA) is well known as a region containing peptides important in feeding (e.g., melanin concentrating hormone, orexin) as well as a region that potently supports electrical self-stimulation. In fact, leptin, the anorectic hormone released from adipocytes, attenuates the ability of fasting to increase self-stimulation of the LHA (Fulton, et al, 2000). Interactions between the LHA and regions important for reward behaviors such as the nucleus accumbens have yet to be described but it is likely that dopaminergic and serotonergic pathways are critical for food reward.…”
Section: Discussionmentioning
confidence: 99%
“…In normal individuals, the orexin modulation of VTA neurons may be important in transmitting information about the availability of primary rewards to the mesocorticolimbic reward system (Schultz, 1998). A subpopulation of orexin neurons possess leptin receptors (Willie et al, 2001), and leptin administration is known to modulate the rewarding effect of lateral hypothalamic stimulation (Fulton et al, 2000). Furthermore, orexin neurons are sensitive to metabolic state, receiving input from glucose-sensitive neurons (Liu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%